Safety and Efficacy of Riluzole in Traumatic Spinal Cord Injury: A Systematic Review With Meta-Analyses - Luke J. Weisbrod; Thomas T. Nilles-Melchert; Judith R. Bergjord; Daniel L. Surdell (Neurotrauma Reports)
Traumatic spinal cord injury (SCI) is a cause of significant morbidity, often resulting in long-term disability. We aimed to compare outcomes after riluzole versus patients who received placebo or standard of care with no specific intervention. MEDLINE, Embase, Scopus, and Cochrane Library database searches yielded 92 records, and five met the study inclusion criteria. Fixed-effect and random-effects models were used to establish odds ratios (ORs) and mean difference (MD) with 95% confidence intervals (CIs) for each outcome. The results of the pooled analysis showed that in patients with acute traumatic SCI, riluzole resulted in increased American Spinal Injury Association (ASIA) motor scores at 3 months (MD 0.26, 95% CI [–0.10,0.61], I2 = 0%; p = 0.157) and 6 months (MD 0.21, 95% CI [–0.17,0.60], I2 = 0%; p = 0.280) and change in ASIA Impairment Scale (AIS) at 3 months (OR 0.59, 95% CI [–0.12,1.30], I2 = 0%, p = 0.101) and 6 months (OR 0.28, 95% CI [–0.50,1.06], I2 = 0%, p = 0.479) in comparison to the control groups, though not to a level of statistical significance. Riluzole resulted in fewer adverse events than the control groups (OR −0.12, 95% CI [–1.59,1.35], I2 = 0%, p = 0.874) and lower mortality (OR −0.20, 95% CI [–1.03,0.63], I2 = 0%, p = 0.640), though also not to a level of statistical significance. These meta-analyses suggest that riluzole for the treatment of traumatic SCI is safe and results in improved neurological outcomes when compared to controls, though not to a level of statistical significance. More robust prospective, randomized studies are necessary to help inform the safety and efficacy of riluzole for traumatic SCI.